EXPLORING THE POTENTIAL OF EDUCATIONAL INSTITUTIONS TO CREATE DEMENTIA-FRIENDLY COMMUNITY MOVEMENTS IN JAPAN - Suzuki, Naoko (PUPIL: International Journal of Teaching, Education and Learning, 2020)
As a nation where more than 28% of the total population is 65 years and over, Japan faces multiple ageing-related issues. Among these, dementia dominates the agenda due to its high societal costs. The purpose of this study was to elucidate the state of the current movement to create dementia-friendly communities across Japan, with a focus on the good practices of educational institutions, such as libraries, museums and lifelong learning centers. A case study approach was employed, which involved site visits and interviews with those charged with the development of educational projects to create dementia-friendly communities. The findings of this research suggest that some educational institutions have created dementia-friendly communities through utilizing their existing rich resources and providing approachable, convenient and holistic learning environments. However, current movements have tended to focus on assisting care givers and ordinary citizens through the provision of appropriate information and through opportunities for exchanging ideas and/or anxieties regarding dementia, and no careful attention has been paid to those living with dementia, whose viewpoints tend to be neglected in most current educational provision. Future research should focus on the ways in which different educational institutions can directly contribute to those living with dementia by hearing their voices and defining the meaning of learning for them; the minute process of transformation by deliberately observing the interaction between persons with dementia and others in such institutions through various methodologies; possibilities of learning for all stakeholders regarding persons with dementia, in order to provide more inclusive dementia-friendly communities. Overall, many opportunities still remain uncultivated and diverse individuals could be involved in this process so that the potential of each institution can be more fully developed in the light of current societal needs.